2022
DOI: 10.3389/fsurg.2022.902710
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Selection of Pathological T-Classification for Non-Small-Cell Lung Cancer in Varying Degrees of Visceral Pleural Invasion: A SEER-Based Study

Abstract: BackgroundThe T classification of non-small-cell lung cancer (NSCLC) was upgraded from T1 to T2 when accompanied by visceral pleural invasion (VPI). However, the association between VPI and prognostic outcomes was obscure in NSCLC patients with ≤3 cm tumor size (TS), which leaded the controversy of selection of T classification. The goal was to evaluate the effect of VPI on the prognosis of NSCLC with ≤ 3cm TS and present a modified T classification.MethodsA total of 14,934 NSCLC patients without distant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The relationship between the degree of VPI and tumor stage has been extensively explored in numerous relevant studies. A retrospective study revealed that in patients with NSCLC without lymph node metastasis and with a tumor diameter of 2 cm or less, tumors with PL1 features should be classified as stage T1, while tumors with PL2 features should be classified as stage T2 ( 43 ). T2a-PL2 tumors were categorized as stage T2b, indicating a poorer prognosis ( 44 ).…”
Section: Visceral Pleural Invasion and Tumor Stagingmentioning
confidence: 99%
“…The relationship between the degree of VPI and tumor stage has been extensively explored in numerous relevant studies. A retrospective study revealed that in patients with NSCLC without lymph node metastasis and with a tumor diameter of 2 cm or less, tumors with PL1 features should be classified as stage T1, while tumors with PL2 features should be classified as stage T2 ( 43 ). T2a-PL2 tumors were categorized as stage T2b, indicating a poorer prognosis ( 44 ).…”
Section: Visceral Pleural Invasion and Tumor Stagingmentioning
confidence: 99%